Are Australian general practice nurses underutilised?: An examination of current roles and task satisfaction. Issue 5 (October 2019) - Halcomb, Elizabeth; Ashley, Christine
Abstract: Background: The general practice nursing workforce in Australia has grown exponentially in the last fifteen years. To understand the contribution and issues relating to this workforce we need to explore the evolution of the nurses' role and the nurses' perceptions of the work that they undertake. Aim: To describe trends in general practice nurse clinical activities, the extent to which GPNs use their knowledge and skills and their satisfaction with the general practice nurse role. Methods: Within a larger mixed methods project, a national cross-sectional survey of Australian primary health care nurses was undertaken. This paper details the survey findings related to the role of nurses working in general practice, the extent to which they use their knowledge and skills and their satisfaction with their role. Data about nurse roles was compared with previous workforce data to elucidate changes over time. Findings: Of the 1166 primary health care nurses who responded to the survey, 950 reported being employed in general practice. Participants reported undertaking activities related to health promotion and chronic disease management more frequently now than previously. They identified a desire to spend the same or less time on administrative activities and more time on health promotion, patient education and patient assessment. Nearly half of participants reported that often they feel that they could do more, or most of the time they don't use their skills to the full extent. Conclusion: Nurses working in general practice are increasingly undertaking activities related to health promotion and chronic disease management. However, these nurses remain underutilised. Having nurses working to their full scope of practice has the potential to increase job satisfaction and nurse retention, as well as improve patient health outcomes.